Supercritical Fluid Extraction from Zataria Multiflora Boiss and Impregnation of Bioactive Compounds in Pla for the Development of Materials with Antibacterial Properties - Galotto-Lopez, M; Rojas-Sepulveda, A (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The chemical composition of the Z. multiflora EO extract obtained by supercritical extraction was identified by GC-MS. DPPH assays demonstrated the antioxidant activity of Z. multiflora EO extract. Z. multiflora EO extract was impregnated in PLA films by supercritical impregnation. The operational parameters of the supercritical impregnation process were optimized using FFD. The impregnated samples were characterized by SEM, FTIR, DSC and XRD. Impregnated PLA films showed antibacterial activity against E. coli and S. aureus. Highlights: In this research, the extraction with supercritical carbon dioxide (SC-CO2) and the subsequent impregnation of the extracted bioactive compounds from Zataria multiflora Boiss (Z. multiflora) into polylactic acid (PLA) films was investigated. The effects of temperature (318 and 338 K), pressure (15 and 25 MPa) and cosolvent presence (0 and 3 mol%) on the extraction yield were studied. The SC-CO2 assisted impregnation runs were carried out in a discontinuous mode at different pressure (15 and 25 MPa), temperature (318 and 328 K), and time (2 and 8 h) values, using 0.5 MPa min−1 as a constant value of depressurization rate. ANOVA results confirmed that pressure, temperature, and time influenced the extraction yield. Moreover, antioxidant activities of extracts of Z. multiflora were evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays. In addition, the antibacterial activities of the extracts were screened against standard strains of Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The results of this investigation indicated that extracts obtained from the aerial parts of Z. multiflora possessed antioxidant and antibacterial properties. The impregnated samples presented strong antibacterial activity against the selected microorganisms. © 2022 by the authors.
Keywords: supercritical solvent impregnation; polylactic acid; Zataria multiflora Boiss; antibacterial active packaging